Response to biologics and clinical remission in the Adult German Asthma Net Severe Asthma Registry Cohort - Milger-Kneidinger, Katrin; Suhling, Hendrik; Skowasch, Dirk; Holtdirk, Annette; Kneidinger, Nikolaus; Behr, Jürgen; Timmermann, Hartmut; Schulz, Christian; Schmidt, Olaf; Ehmann, Rainer; Hamelmann, Eckard; Idzko, Marco; et al. (The journal of allergy and clinical immunology. In practice, 2023)
Background - Recently, criteria for evaluation of response to biologics have been proposed and the concept of clinical remission has gained attention as a possible goal even in severe asthma. - Objective - To analyze the response and remission in the German Asthma Net severe asthma registry cohort. - Methods - We included adults not using a biologic at baseline (V0) and compared patients treated between V0 and 1-year visit (V1) without using a biologic (group A) to patients starting with a biologic after V0 and continuing it up to V1 (group B). We applied the Biologics Asthma Response Score to quantify composite response in good, intermediate, or insufficient. We defined clinical remission (R) as absence of significant symptoms (Asthma Control Test score ≥ 20 at V1) in the absence of exacerbations and oral corticosteroid therapy. - Results - Group A included 233 and group B 210 patients, the latter receiving omalizumab (n = 33), mepolizumab (n = 40), benralizumab (n = 81), reslizumab (n = 1), or dupilumab (n = 56). At baseline, group B had less often an allergic phenotype (35.2% vs 41.6%), lower Asthma Control Test score (median, 12 vs 14), more exacerbations in the past year (median, 3 vs 2), and more often high-dose inhaled corticosteroid treatment (71.4% vs 51.5%) than group A. After 1 year of treatment, rates of response (good: 61.4% vs 34.8%; intermediate: 26.7% vs 42.9%; insufficient: 11.9% vs. 22.3%) and/or clinical remission (37.6% vs 17.2%) were higher in group B than in group A. - Conclusions - Despite more severe asthma at baseline, patients treated with biologics had a markedly higher probability of achieving good clinical response and/or remission than patients treated without biologics.